Biochemical and Molecular Analysis of Staphylococcus aureus Clinical Isolates from Hospitalized Patients - Amit Karmakar; Parimal Dua; Chandradipa Ghosh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Staphylococcus aureus is opportunistic human as well as animal pathogen that causes a variety of diseases. A total of 100 Staphylococcus aureus isolates were obtained from clinical samples derived from hospitalized patients. The presumptive Staphylococcus aureus clinical isolates were identified phenotypically by different biochemical tests. Molecular identification was done by PCR using species specific 16S rRNA primer pairs and finally 100 isolates were found to be positive as Staphylococcus aureus. Screened isolates were further analyzed by several microbiological diagnostics tests including gelatin hydrolysis, protease, and lipase tests. It was found that 78%, 81%, and 51% isolates were positive for gelatin hydrolysis, protease, and lipase activities, respectively. Antibiogram analysis of isolated Staphylococcus aureus strains with respect to different antimicrobial agents revealed resistance pattern ranging from 57 to 96%. Our study also shows 70% strains to be MRSA, 54.3% as VRSA, and 54.3% as both MRSA and VRSA. All the identified isolates were subjected to detection of mecA, nuc, and hlb genes and 70%, 84%, and 40% were found to harbour mecA, nuc, and hlb genes, respectively. The current investigation is highly important and informative for the high level multidrug resistant Staphylococcus aureus infections inclusive also of methicillin and vancomycin.